2013
DOI: 10.1007/s00705-013-1829-x
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of polyethylenimine as a candidate for novel prophylactic therapeutics against genital herpes caused by herpes simplex virus

Abstract: Herpes simplex virus types 1 (HSV-1) and 2 (HSV-2) cause genital herpes, which can enhance the acquisition of human immunodeficiency virus. The development of anti-HSV agents with novel mechanisms of action is urgently required in the topical therapy of genital herpes. In this study, the in vitro and in vivo anti-HSV effects of Epomin SP-012(®), a highly cationic polyethylenimine, were evaluated. When the in vitro antiviral effects of SP-012 were assessed, this compound showed potent activity against HSV-1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Further, clinical relapse in the latter group was milder and transient suggesting that AGMA1 reduces the number of latently infected cells and the potential for virus reactivation. In all, in vivo tests indicate that AGMA1 provides significant protection against HSV infection and disease and compares favorably well with dendrimers and polyanions considered good candidate topical microbicides [18e21, 34,58,75,76].…”
Section: Tablementioning
confidence: 99%
“…Further, clinical relapse in the latter group was milder and transient suggesting that AGMA1 reduces the number of latently infected cells and the potential for virus reactivation. In all, in vivo tests indicate that AGMA1 provides significant protection against HSV infection and disease and compares favorably well with dendrimers and polyanions considered good candidate topical microbicides [18e21, 34,58,75,76].…”
Section: Tablementioning
confidence: 99%
“…Through these observations, we can say that multiple antibiotics encapsulated single type nanoparticle can inhibit the growth of different bacteria and increase the effects. Based on the present results, SNP can be the choices of nanoparticles to encapsulate antibiotic/drug or immobilize important biomarkers and the current study may also be mimicked for other potential biomolecules such as industrially important enzymes or aptamer or other biomolecules (Poongodi et al, 2002;Anbu et al, 2006;Hayashi et al, 2014;Chen et al, 2014Chen et al, , 2015Tan et al, 2015;Azhdarzadeh et al, 2016;Phang et al, 2016;Soo et al, 2016) toward downstream applications. Previously, Mohan Yallapu et al (2012) have revealed the drug loading on different nanoparticles and shown cellulose nanoparticle has higher efficiency to load the curcumin to prevent prostate cancer.…”
Section: Effect Of Antibiotic-loaded Snpmentioning
confidence: 88%
“…Other polymers have been synthesized that do not require sulfate groups to effectively inhibit HSV infection. Polymers with a polycationic character have been widely studied in the field: polylysine, polyarginine, polyacrylates, viologen (4,4′-bipyridinium salts) dendrimers, polyethylenimine, poly­(amidoamine)­s, poly­(ethylene glycol)- block -poly­(3-(methacryloyl­amino)­propyl trimethyl­ammonium chloride), and oligoamines conjugated to dextran as well as other cationic dextran derivatives. , Possible mechanisms of action include destabilizing cell membranes, electrostatically interacting with the envelope of lipid-enveloped viruses, or inhibiting virus–cell surface interactions by binding to negatively charged cell surface heparan sulfate. ,, In some instances, such as AGMA1 poly­(amidoamine)­s or Eudragit E100, these polymers could potentially be applied as microbicides. , …”
Section: Herpes Simplex Virusmentioning
confidence: 99%